Peran Unit Usaha Mikro, Kecil dan Menengah (UMKM) dalam Mengurangi Tingkat Pengangguran Masyarakat - Chairun Nissa; Nurkomaria Nurkomaria; Salwa Apriliza (STIKes Ibnu Sina Ajibarang, 2025)
This article analyzes the role of Micro, Small, and Medium Enterprises (MSMEs) in reducing unemployment in Indonesia. This article uses a literature study method with a qualitative approach, data is collected from various sources to analyze the contribution of MSMEs to employment and economic growth. Results show that MSMEs supply more than 60% of employment, but face challenges such as limited skills and infrastructure. Government support, including digitization policies and training, is crucial to improve MSME competitiveness. The conclusion of this article emphasizes that digitalization and strengthening business networks are key to strengthening the position of MSMEs, which in turn can have a positive impact on the economy and community welfare.